Pengaruh Thought Stopping terhadap Kecemasan Mengikuti SBMPTN pada Siswa Kelas II SMAN 2 Gerung Kabupaten Lombok Barat - Ika Puspita Sari; I Made Eka Santosa; Ni Made Sumartyawati; Ns Suhartiningsih (STIKES Mataram, 2022)
The number of participants for the 2021 SBMPTN was 777,858 people. 184,000 students were declared to have passed the 2021 SBMPTN in which the percentage of acceptance was 25.28 percent. Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia (2021). The large percentage of not passing the SBMPTN in 2021 for some participants cam be felt as a stressor that can cause anxiety because many students want to enter higher education in this path. Anxiety is a feeling that can happen to almost anyone at some point in their life span. Symptoms felt by students are dizziness, nausea, defecation, insomnia, etc. This study aims to determine the effect of Thought Stopping on anxiety following the SBMPTN in class XII of SMAN 2 Gerung West Lombok.The population in this study were students of class XII, amounting to 47 respondents, with a sample of 47 respondents obtained by the total sampling technique, The anxiety was measure using the Zung Self Rating Anxiety Scale questionnaire. The effect of giving Thoughts Stopping exercises was measured using the Paired Samples T-Test analysis test. .The results showed that before the Thought Stopping treatment the mean was 3.1489, and after the Thought Stopping treatment, the mean was 2.2979. the results of the Paired Samples T-Test showed a p-value < (0.000<0.05), then Ha was accepted and H0 was rejected.The study concludes that there is an effect of giving Thought Stopping on reducing the anxiety level of class XII adolescents who take part in the SBMPTN SMAN 2 Gerung West Lombok. Thus, is it good to be applied to provide therapy to students who will take the SBMPTN exam. Keywords: Anxiety, Thought Stopping.